Diagnosis and treatment of gastroduodenal telangiectasias - Sojo, Enrique; Estapé, Gonzalo; Vázquez, Graciela; Ruocco, Álvaro; Pike, Alexander (Cirugía del Uruguay, 1978)
After six thousands fiberscope examinations of the upper gastrointestinal tract, ene thousand five hundred of them were due to upper digestive hemorrhage. Among these, it was p:ssible to certify that eighteen patients bled from vascular telangiectasic malformations ( 1. 2 % of the upper digestive hemorrhage). In only three cases it was possible to certify that they belonged to the Rendu-Osler-Weber síndrome. Clinic and radiclogic signs are analized, emphasizing that correct diagnosis was possible in every patient onl'y by fiberscope examination. Endoscopie aspects of these lesions, distribution, topography and number as well as coexisting lesions are described. Pointing out different techniques, radio1ogical or intraoperative that enable the lesiona} extension diagnosis in the digestive tract further than the duodeno- jejunal angle. Finally, after analizing surgery and procedures used in the treatment, the commend endoscopic electro-coagulation telangiectasias.